PENGARUH BEBAN TEKAN TERHADAP KEMAMPUAN EKSTRAKSI MASSA CAIR SLURRY OLEH “ALAT PEMISAH FASES-URINE SAPI” YANG DIOPERASIKAN SECARA MANUAL - Nurpatria, N.; Padang, Yesung Allo (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2011)
Cow manure can be used as a source of energy and as a solid or liquid fertilizer. An adult cow can produce fases (solid manure) to 23 kg/day and urine (liquid manure) 9 kg/day. Three or four cow is capable to fullfill the dayly needs of cooking fuel for one rural household. Cow manure slurry can also be convert as fertilizer, that is liquid fertilizer which is derived from urine and solid fertilizer originating from the solids. Solid and liquid from cow manure is usually mixed, therefore to make the liquid and solid fertilizer, the liquid and solid masses need to be separated first. Recent separators of fases and urine are are electrical energy driven, so that those kind of device could not be used in the rural areas where the electric grid supply were not available. So that a model of a faces-urine separator of cow manure slurry is utilize which was constructed for manual pressing force. Moreover, through this research It have had created a manual fases-urine separator which only requires one operator. The separator consists of main parts including; lever press, chamber press, fases-urine separation mechanism, the mechanism of loading-unloading, and ajustment mechanism for pressing pressure. This design is capable of performing the separation in a wide range of pressing force and it only requires one operator. Results Show That the model is capable to separate liquid from the slurry as much as 13.9% at a pressing force of 14 kg the which is applied for 18 seconds.